Going Granular: Equity of Health Financing at the District and Facility Level in India - Urmila Chatterjee; Owen Smith (Taylor & Francis Group, 2021)
Health financing equity analysis rarely goes below the state level in India. This paper assesses the equity and effectiveness of public spending on health in the state of Odisha. Using district-level public spending data for the first time, it sheds light on the incidence of public spending by geography and by type of services. There are three key findings. First, it identifies the weak link between district spending and district need, proxied by poverty rates or lagging sectoral outcomes, highlighting the potential for a more needs-based approach to public resource allocation. Second, the results indicate that at the household level health spending by the state is not pro-poor, especially in public hospitals, underscoring the need to improve access to care for the bottom 40% at these facilities. Third, an exhaustive analysis of micro-level treasury data brings into focus the importance of reforming public finance data systems to support evidence-based policy at the sub-state level. Significant district-wise variation in key health financing and equity indicators, combined with growing policy interest in the district level, underscore the utility of further empirical work in this area.